Karakterisasi Enzim Pemecah Pati dari Malt Serelia - Phieter, Alvina Cornelia; Chrisnasari, Ruth; Pantjajani, Tjandra (Keluwih: Jurnal Sains dan Teknologi, 2020)
Abstract- Starch-degrading enzymes not only can be found in bacteria and fungi, but also in plants. Some plants that produce starch-degrading enzymes are germinated grain of sorghum, maize, and mung bean. pH and temperature are factors that can affect the activity of enzyme. Effect of pH and temperature to starch-degrading enzyme activity of these 3 cereal grains are reported in this research. Grain of sorghum, maize, and mung bean were germinated for 2 days and dried to produce malt. Enzymes from these 3 different malts were extracted using 7 buffers with different pH (4.5, 5, 5.5, 6, 6.5, 7) . Buffer that produced highest enzyme activity based on degradation of starch as a substrate (iodine-starch method) and based on formation of reducing sugars as products (DNS method) would be used for determining the effect of temperatures (20 °C, 30 °C, 40 °C, 50 °C). Effect of pH and temperatures to enzyme activity from 3 different malts tend to be fluctuating. Sorghum malt had the highest enzyme activity per gram malt based on degradation of starch activity test. Estimated enzyme activity of sorghum malt was 103,82 mg.g- 1.min-1. Maize malt had the highest enzyme activity based on formation of reducing sugars activity test. Estimated enzyme activity of maize malt was 13.08 mg.g-1.min-1. Keywords: amylase enzyme, sorghum malt, maize malt, mung bean malt, pH temperature Abstrak- Enzim pemecah pati dapat diperoleh dari tanaman selain dari bakteri dan fungi. Beberapa jenis tanaman yang memiliki enzim pemecah pati adalah biji sorgum, jagung, dan kacang hijau yang berkecambah. pH dan suhu merupakan beberapa faktor yang mempengaruhi aktivitas dari enzim. Pengaruh pH dan suhu terhadap aktivitas enzim amilase dari ketiga jenis biji ini akan diamati dalam penelitian ini. Biji sorgum, jagung, dan kacang hijau dikecambahkan selama 2 hari dan dikeringkan untuk menghasilkan malt. Enzim dari ketiga jenis malt ini akan diekstrak menggunakan 7 buffer pH berbeda yaitu buffer pH 4,5; 5; 5,5; 6; 6,5 dan 7. Buffer yang menghasilkan nilai aktivitas enzim tertinggi berdasarkan degradasi substrat pati (metode pati-iodin) dan berdasarkan pembentukan produk gula reduksi (metode DNS) akan digunakan lebih lanjut untuk melihat pengaruh suhu yaitu suhu 20 °C, 30 °C, 40 °C, dan 50 °C. Pengaruh pH dan suhu terhadap aktivitas enzim ketiga jenis malt cenderung fluktuatif. Malt sorgum memiliki nilai aktivitas enzim per gram malt tertinggi berdasarkan uji aktivitas degradasi substrat pati (metode pati-iodin) yaitu 103,82 mg.g-1.min-1 dan malt jagung memiliki nilai aktivitas enzim per gram malt tertinggi berdasarkan uji aktivitas pembentukan gula reduksi (metode DNS) yaitu 13,08 mg.g-1.min-1. Kata kunci: amylase enzyme, sorghum malt, maize malt, mung bean malt, pH temperature